GAMBARAN TINGKAT KEPUASAN PASIEN RAWAT INAP TERHADAP PELAYANAN KEPERAWATAN (Studi Deskriptif di RSUD Pare Diruang Flamboyan Pare Kabupaten Kediri Tahun 2014) - Ridwan, Achmad; Anto, Febri Dwi (Jurnal AKP, 2014)
Patient satisfaction is the current state of desire, expectations and patient needs can be met. A service is considered satisfactory if the service can meet the needs and expectations of patients. The purpose of this study is how the image of the level of patient satisfaction after nursing care given in hospitals Pare.            The study design is descriptive. The population was patients in flamboyant space with the number of samples of 30 patients with 30 respondents taken with accidental sampling technique. The research variables are the level of patient satisfaction to nursing service kuesioner collected using the number 25 queries. The resulting data is processed by means of editing, cording, scoring, tabulating and analyzed by percentage. The data presented in the form of diagrams and tables .            From the results, over almost half of the respondents are very satisfied with nursing care as much as 19 respondents ( 63.3 % ) and who say satisfied as much as 10 respondents ( 33.3 % ) and that says quite satisfied as much as 1 respondent (3,3%) of total of 30 respondents.            In connection with the above results in order to maintain the quality of nursing care in the hospital ranging from physical means or facility space is adequate, the officer gave service with a friendly, courteous, professional and reliable. Concluded that the quality of nursing care in hospitals Pare Kediri district has been judged to be satisfactory. it is recommended that existing services be maintained or optimized. Keywords : satisfaction , nursing services